Skill Training Periodization in “Specialist” Sports Coaching—An Introduction of the “PoST” Framework for Skill Development - Otte, Fabian W.; Millar, Sarah-Kate; Klatt, Stefanie (Frontiers in Sports and Active Living, 2019)
Across sports and movement science, training periodisation has been recognised as key for athlete development and performance. While periodisation with regard to physiology has a proven history, the structuring and periodisation of motor learning and skill development is seemingly less researched and practiced. Despite the existence of numerous theoretical accounts underpinning skill acquisition training and more recently emerging periodisation models, a cohesive conceptual framework to support practitioners on the ground in adequately periodising skill training environments appears to be needed. In order to fill this gap, the current conceptual paper seeks to review and transfer contemporary skill acquisition training theory (driven by the constraints-led approach) into a practically-applicable ‘Periodisation of Skill Training’ framework (‘PoST’ framework). This framework provides valuable conceptual and practical support for coaches, so as to enhance adaptive movement variability for sport skills and manipulate skill training environments (i.e., on the macro-level for the periodisation of training over the course of multiple training sessions and on the micro-level for the microstructure of single training sessions). Practical examples from the football goalkeeper context underline the proposed conceptual framework.